2019
DOI: 10.1039/c8ta11330k
|View full text |Cite
|
Sign up to set email alerts
|

Salen–porphyrin-based conjugated microporous polymer supported Pd nanoparticles: highly efficient heterogeneous catalysts for aqueous C–C coupling reactions

Abstract: Salen–porphyrin-based CMP supported Pd nanoparticles were employed as high-performance heterogeneous catalysts for aqueous Suzuki–Miyaura and Heck–Mizoroki coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 60 publications
0
59
0
Order By: Relevance
“…20 Hence, a prudent choice of support is vital. Silica, 21,22 polymers, 23,24 zeolites, 25,26 alumina, 27,28 magnetic nanoparticles, 29,30 and carbon 31 have emerged as excellent support systems. They reportedly achieve almost quantitative conversion and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Hence, a prudent choice of support is vital. Silica, 21,22 polymers, 23,24 zeolites, 25,26 alumina, 27,28 magnetic nanoparticles, 29,30 and carbon 31 have emerged as excellent support systems. They reportedly achieve almost quantitative conversion and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Thus,w es peculated that salen-containing frameworks and polymers may display good electrocatalytic OER performance, because salen-CMPs combine the rigid conjugated porous structure of CMPs and the intrinsic electrocatalytic activity of the salen moiety. [24][25][26][27][28][29][30] In this work we have demonstrated the ability of salen-containingp olymers to act as electrocatalysts for the first time. The electrochemical test results showed that the catalyst salen-CMP-Fe-3 showed the highest OER activity.W hen loaded onto glass carbon electrodes, the prepared salen-CMP-Fe-3 electrodes demonstratedas mall Tafel slope of 63 mV dec À1 and an overpotentialo f2 38 mV at 10 mA cm À2 in 0.1 m KOH.…”
Section: Introductionmentioning
confidence: 80%
“…In recent years, there has been a rapid growth in the development of novel supported compounds such as supported catalysts, reagents, sensors and adsorbents. [1][2][3][4][5][6][7] Therefore, nanoparticles have been widely used as solid supports for the immobilization of homogeneous catalysts. [8][9][10] For example, silica materials, [11] polymers, [12] graphene oxide, [13][14][15][16] carbon nanotubes, [17] iron oxide, [18] ionic liquids, [19,20] boehmite nanoparticles, [21,22] biochar, [23] magnetic nanoparticles, [24][25][26] etc.…”
Section: Introductionmentioning
confidence: 99%